1997
DOI: 10.1177/000841749706400105
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Play for Young People with Physical Disabilities

Abstract: As a primary area of occupation, play is central to the lives of children. Emerging views of play reflect the complexity of the area, and focus on the relationship between the person and the environment during play. This paper reports the results of a qualitative study of twenty adolescents with and without physical disabilities. The participants were interviewed about their perceptions and personal experiences of play. Through a textual analysis of the data, significant themes related to the nature of play, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 10 publications
3
59
0
Order By: Relevance
“…Play was defined as a necessary and primary occupation for children (Sturgess, 2003). Play included the following characteristics: it is internally motivated or rewarding; focuses more on actions rather than outcome; goes beyond reality as well as reflects it; relates to an attitude that a child brings to an activity as opposed to the activity itself; is controlled by the individual; is spontaneous; can be done individually or with peers; and, is fun and pleasurable (Pollock et al, 1997;Stagnitti, 2004;Sturgess, 2003). Childcare center was defined as licensed public or private early-years settings, such as nursery school, public-or home-based daycare, or preschool (Vanderloo, Tucker, Ismail, & van Zandvoort, 2012).…”
Section: Definitionsmentioning
confidence: 99%
“…Play was defined as a necessary and primary occupation for children (Sturgess, 2003). Play included the following characteristics: it is internally motivated or rewarding; focuses more on actions rather than outcome; goes beyond reality as well as reflects it; relates to an attitude that a child brings to an activity as opposed to the activity itself; is controlled by the individual; is spontaneous; can be done individually or with peers; and, is fun and pleasurable (Pollock et al, 1997;Stagnitti, 2004;Sturgess, 2003). Childcare center was defined as licensed public or private early-years settings, such as nursery school, public-or home-based daycare, or preschool (Vanderloo, Tucker, Ismail, & van Zandvoort, 2012).…”
Section: Definitionsmentioning
confidence: 99%
“…The view of play as an occupation shifts the focus away from just the effects of play on the development of the child, to encompass the transaction between the child and the environment. 10 In the area of physical development, active engagement in physical games and sports has been shown to help children and adolescents learn about their bodies and how to react to the environment. 11 Engagement in physical play also serves to develop self-competence, as was found by a study which showed that children and adolescents who engaged in physical play are more self-confident, outgoing, and socially adjusted.…”
Section: Play and Child Developmentmentioning
confidence: 99%
“…16 A qualitative study looking at the perceptions of play for young people with and without disabilities found that young people with disabilities report environmental and personal barriers as having an impact on their play. 10 Recent advances in the area of VR technology may facilitate the active engagement of children with disabilities in play activities.…”
Section: Play and Children With Disabilitiesmentioning
confidence: 99%
“…Garvey (1991) described play as self-initiated, voluntary behaviour, which is non-obligatory, has no extrinsic goals and is free from externally imposed rules. When children are asked to distinguish between 'work' and 'play' activities they generally describe the activities that they have chosen and directed themselves and which are free of adult control as 'play' (Pollock et al, 1997).…”
Section: Coopermentioning
confidence: 99%
“…The presence of other children, parents or adults will also affect how a child plays or interacts with the human objects in his or her environment (Coster, 1998). All of these factors influence how a child responds in play to the physical and social challenges presented by the environmental context (Schaaf and Mulrooney, 1989;Pollock et al, 1997). For example, children are more likely to play in a safe, familiar, nurturing environment, whereas an unfamiliar setting or novel play objects may elicit more exploratory or non-play behaviour (Morrison et al, 1996).…”
Section: The Play Environmentmentioning
confidence: 99%